2013
DOI: 10.2337/dc13-0701
|View full text |Cite
|
Sign up to set email alerts
|

Vital Signs, QT Prolongation, and Newly Diagnosed Cardiovascular Disease During Severe Hypoglycemia in Type 1 and Type 2 Diabetic Patients

Abstract: OBJECTIVETo assess vital signs, QT intervals, and newly diagnosed cardiovascular disease during severe hypoglycemia in diabetic patients. RESEARCH DESIGN AND METHODSFrom January 2006 to March 2012, we conducted a retrospective cohort study to assess type 1 and type 2 diabetic patients with severe hypoglycemia at a national center in Japan. Severe hypoglycemia was defined as the presence of any hypoglycemic symptoms that could not be resolved by the patients themselves in prehospital settings. RESULTSA total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 39 publications
(80 reference statements)
6
88
1
8
Order By: Relevance
“…Since the ACCORD and VADT results were published, attempts have been made to assess whether a relationship exists between hypoglycemia and CV risk or mortality, but only recently has a consensus begun to emerge suggesting that there is a link between the two (6,8,9). Several potential mechanisms linking hypoglycemia and CV risk have been proposed, including QT prolongation, hemodynamic changes arising from catecholamine release, inflammation, and endothelial dysfunction (23)(24)(25). Although real, these effects are more likely to explain a transient increase in CV risk during the acute phase of hypoglycemia rather than the longer-term relationship observed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Since the ACCORD and VADT results were published, attempts have been made to assess whether a relationship exists between hypoglycemia and CV risk or mortality, but only recently has a consensus begun to emerge suggesting that there is a link between the two (6,8,9). Several potential mechanisms linking hypoglycemia and CV risk have been proposed, including QT prolongation, hemodynamic changes arising from catecholamine release, inflammation, and endothelial dysfunction (23)(24)(25). Although real, these effects are more likely to explain a transient increase in CV risk during the acute phase of hypoglycemia rather than the longer-term relationship observed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…A surrogate measure of myocardial perfusion during hypoglycemia in young adults with and without type 1 diabetes has recorded lower values in the group with diabetes (23). How often severe hypoglycemia may cause myocardial infarction is unknown, as only a few anecdotal cases have been reported, while a large retrospective Japanese study of 414 subjects presenting with severe hypoglycemia revealed newly diagnosed vascular disease in five patients (with only 1 case of myocardial infarction and 4 cases of cerebrovascular disease) (24).…”
Section: Cardiovascular Effects Of Hypoglycemiamentioning
confidence: 99%
“…This has been demonstrated in both type 1 and type 2 diabetes (24,(29)(30)(31). QT prolongation is a strong risk factor for severe ventricular arrhythmia and sudden death (32) and has been suggested as an explanation for the "dead in bed" syndrome of patients with type 1 diabetes (29).…”
Section: Cardiovascular Effects Of Hypoglycemiamentioning
confidence: 99%
“…Estimated GFR was calculated using the following formula10: estimated GFR (mL/min/1.73normalm2false)=194×(serum creatininelevel,0.333333emmg/dL)1.094×(age,years)0.287false(×0.7390.333333emif the patientwas a womanfalse). A severe hypoglycemic episode was defined as the presence of any hypoglycemic symptoms that could not be resolved by the patients outside a hospital setting, and that required medical assistance after visiting the emergency room by ambulance11. Cardiovascular disease included angina, myocardial infarction, stroke and transient ischemic attack.…”
Section: Methodsmentioning
confidence: 99%